Behavioral profiling of SLC38A10 knockout mice using the multivariate concentric square fieldTM test - Lindberg, Frida A.; Roman, Erika; Fredriksson, Robert (Frontiers in Behavioral Neuroscience, 2022)
Introduction SLC38A10 is a gene that encodes the SLC38A10 protein, also known as SNAT10. The SLC38 family is evolutionary old, and SLC38A10 is one of the oldest members of the family. It is ubiquitously expressed, and its substrates are glutamine, glutamate, alanine, aspartate, and serine. However, little is known about its biological importance. Methods In the current study, an SLC38A10 knockout mouse was run in the multivariate concentric square fieldTM (MCSF) test. The MCSF test gives the mouse a choice of areas to explore; sheltered areas, elevated and illuminated areas, or open spaces, and a behavioral profile is obtained. The multivariate data obtained were analyzed (i) for each parameter, (ii) parameters grouped into functional categories, and (iii) with a principal component analysis. Results In the trend analysis, knockout mice had a decreased exploratory behavior compared to controls but did not show a distinct grouping in the principal component analysis. Discussion There was not a pronounced difference in the behavioral profile in SLC38A10 knockout mice compared to their wild-type controls, although subtle alterations in zones associated with exploratory behavior and risk assessment in female and male knockout mice, respectively, could be observed. These results imply that a loss of function of the SLC38A10 protein in mice does not drastically alter behavior in the MSCF test.